Study on Vibration Response of Layered Media under the Impact Load - Mengyang Zhen; Jun Liu; Zhimin Xiao; Futian Zhao; Yue Wang; Chen Ou; Zheng Liu; Haowen Zheng (Shock and Vibration)
To study the vibration response of the layered medium under impact loading, single-layer concrete slabs, multilayer concrete slabs, and multilayer concrete slabs with a cemented filling layer were used as the working media to simulate the layered medium. A large number of impact loading tests were carried out by using a simple drop hammer device designed by us. The experimental results indicate that, under the impact load, the vibration response of the surface of the medium decreases with the increase in the distance to the impact source, showing the law of fast attenuation near field and slow attenuation far field, and the vibration energy moves to the low-frequency component; the vibration response increases with the increase in the impact energy, and the difference in the vibration response caused by the impact energy decreases as the distance increases; the vibration response is negatively correlated with the thickness of the dielectric layer, and the divergence of vibration response caused by impact energy decreases with the increase in the thickness of the dielectric layer. Due to the existence of the free surface and bedding, the vibration response of the layered medium surface increases with the increase in the number of layers and the vibration velocity response increases with the increase in the distance to the impact source when it is close to the free surface and far from the vibration source. For the filling of the cemented layer, the vibration response of the layered concrete slab becomes more complex under impact loading, showing obvious disorder. At the same time, this paper also used the dimensional analysis method to establish the calculation model of the peak response of vibration velocity of layered media under the impact load, which provided an idea for determining the peak response of vibration velocity of the layered media.